Pengaruh Strategi Mnemonic Terhadap Motivasi Belajar Siswa Materi Lapisan Atmosfer di Sekolah Dasar - Rahmawati, Zulia; Pratiwi, Emy Yunita Rahma; Saini, Ashok (Prodi Pendidikan Guru Sekolah Dasar, 2024)
Current technological developments have changed people’s lifestyles from children to adults in seeking entertainment, one which is gadgets. In this day and age, it is very rare to find people who live without using gadgets. This causes motivation to learn to decrease due to excessive use of gadgets and lack of parental supervision at home so that this can have an impact on enthusiasm for learning. This research aims to determine the effect of mnemonic strategies on students’ learning motivation in class V atmospheric layers material at SD Negeri Rejoagung 3. This research is a quantitative research with a Pre-Experimental Design research type with a One Group Pre-Test Post-Test design. The population is all class V students at SD Negeri Rejoagung 3, totaling 18 students. The methods used to collect data are questionnaires and documentation. The results of this research are: (1) The application of mnemonic strategies in learning can attract students’ attention and enthusiasm for learning. Mnemonic strategies can also help students remember and memorize lesson material easily. (2) Students’ learning motivation in class V atmospheric layers at SD Negeri Rejoagung 3 before using the mnemonic strategi was categorized as moderate with an average score of 72,06. Meanwhile, students’ learning motivation after using the mnemonic strategy increased to 109,33. (3) There was an influence between the mnemonic strategy on students’ learning motivation in class V atmospheric layers at SD Negeri Rejoagung 3 based on the results of the t test with a significance value of 0,000 < 0,05.